Potential antidepressant effects of a dietary supplement from the chlorella and lion's mane mushroom complex in aged SAMP8 mice - Chou, Ming-Yu; Ho, Jou-Hsuan; Huang, Mao-Jung; Chen, Ying-Ju; Yang, Mei-Due; Lin, Liang-Hung; Chi, Ching-Hsin; Yeh, Chin-Hsi; Tsao, Tsui-Ying; Tzeng, Jian-Kai; Hsu, Rachel Jui-cheng; Huang, Ping-Hsiu; et al. (Frontiers in Nutrition, 2022)
Since the 1990s, the prevalence of mental illnesses, such as depression, has been increasing annually and has become a major burden on society. Due to the many side effects of antidepressant drugs, the development of a complementary therapy from natural materials is an urgent need. Therefore, this study used a complex extract of chlorella and lion's mane mushroom and evaluated its antidepressant effects. Six-month-old male senescence-accelerated mice prone-8 (SAMP8) were divided into positive control; negative control; and low, medium, and high-dose groups. All groups were treated with corticosterone (CORT) at 40 mg/Kg/day for 21- days to induce depression in the animals, and the effects of different test substances on animal behavior was observed. The positive control group was intraperitoneally injected with a tricyclic antidepressant (Fluoxetine, as tricyclic antidepressant), the control group was given ddH2O, and the test substance groups were administered test samples once daily for 21 days. The open field test (OFT) and forced swimming test (FST) were applied for behavior analyses of depression animal models. The OFT results showed that the mice in the positive control and the medium-, and high-dose groups demonstrated a significantly prolonged duration in the central area and a significantly increased travel distance. In the FST, the positive control and the medium, and high-dose groups displayed significantly reduced immobility times relative to the control group. The blood analysis results showed significant decreases in triglyceride and blood urea nitrogen levels relative to the positive control and the medium- and high-dose groups. Notably, in the positive control and the medium- and high-dose groups, brain-derived neurotrophic factor (BDNF) increase by more than in the control group. In summary, medium and high dose of extract of chlorella and lion's mane mushroom could improve depression behavior in animals and have the potential to be antidepressant health care products.